Evaluating the Investment Climate in Algeria from an Institutional Point of View & its Impact on Attracting Foreign Direct Investment - in Comparison with Some Arab Countries – - بولعجين, فايزة (Milev Journal of Research and Studies, 2020)
The study aims to demonstrate the importance of the quality of institutions in attracting foreign direct investment, by assessing the institutional investment climate in Algeria and comparing it with some Arab countries (Morocco, Saudi Arabia, the UAE), by relying on some international indicators that measure institutional investment climate. So that the study finds that the quality of institutions in Algeria It is still weak compared to the countries selected for comparison, and that countries that were characterized by better institutional quality attracted more direct foreign investment.